Enhancing Risk Mitigation in Global Software Development: Leveraging Agile Practices and Seven Risk Management Principles - Javed, Maria; Alam, Muhammad Haroon; Sohail, Muhammad; Arif, Fahim (International Conference on Communication Technologies (Online), 2025)
Management of geographically dispersed teams introduces several challenges, particularly the risk during the Global Software Development (GSD) process. It impacts the aim of organizations of cost reduction, benefits of global talent, and rapid product development. Failure to identify and mitigate risks can cause delays in the development process, budget overruns, and compromised quality. In our research the RMMM (Risk Mitigation, Monitoring, and Management) framework was developed, combining seven core risk management principles with agile practices to improve risk handling and enhance team communication and collaboration. The framework focuses on identifying, analyzing, and mitigating risks while ensuring clear communication protocols, realistic project timelines, appropriate tools, and skilled team members. The framework is validated through expert feedback, after results and analysis, the proposed framework demonstrates a 66.7% comprehensive rate. Over 75% of industry specialists support its implementation, with more than 55% considering it feasible for GSD projects. This approach has proven effective in minimizing risks and ensuring successful project delivery in complex, distributed development environments.